Analisis Risiko Kerentanan Pekerja Informal di Indonesia Tahun 2022 - Dewantoro, Fuad Ramdhan (LPPM Universitas BSI, 2024)
Informal workers are vulnerable to various social risks such as poverty, unemployment, and quality and opportunity of work issues. This vulnerability is due to their unprotected status under labor laws or government policies and programs. This research aims to estimate the probability and impact of vulnerability risk occurrence among informal workers in Indonesia in 2022 using K-means cluster and probit regression analysis. The variables used to cluster informal workers' vulnerability status are monthly income, financial recording, education period, working period, technology usage, weekly working hours, and age. The probability value is obtained from the proportion of vulnerable informal workers to the total informal workers. The probit regression analysis tests the significance of the seven independent variables in forming the vulnerability status. The results show that the probability of vulnerability-risk occurrences among informal workers is 0.4578. Vulnerable informal workers are characterized by low income, education level, working hours, lack of technology usage and financial recording, older age, and considerable working periods. All seven independent variables significantly influence the clustering of informal workers vulnerability status. The research implications expect the government to issue policies focusing on vulnerable informal workers, especially in improving their income, education level, working hours, technology usage, financial recording, and old age.